(untitled) (Global Journal of Medical Research, 2018)
A foreign body in the rectum (FBR) is becoming a common presentation in the surgical emergency department. Generally, rectal foreign body removal can be a challenge as regards management due to the wide variety of objects inserted in the rectum. Usually, a rectal foreign body is extracted manually in the emergency department under local anesthesia. In some cases, simple manual extraction of an impacted FBR is unsuccessful. In such cases, general anesthesia with surgical intervention may be required to extract the FBT. We describe the case of a 38-y-old previously healthy male, who presented to the emergency department with rectal bleeding and constant pain in the anal area for approximately three h after inserting a lubricant gel container transanally for autoerotic purposes. Proctoscopy was performed in the emergency department to retrieve the FBR.